Tacrolimus- and Mycophenolate-Mediated Toxicity: Clinical Considerations and Options in Management of Post-Transplant Patients - Alan D. Kaye; Shivam S. Shah; Coplen D. Johnson; Adalyn S. De Witt; Austin S. Thomassen; Charles P. Daniel; Shahab Ahmadzadeh; Sridhar Tirumala; Kristin Nicole Bembenick; Adam M. Kaye; Sahar Shekoohi (Current Issues in Molecular Biology)
Tacrolimus and mycophenolate are important immunosuppressive agents used to prevent organ rejection in post-transplant patients. While highly effective, their use is associated with significant toxicity, requiring careful management. Tacrolimus, a calcineurin inhibitor, is linked to nephrotoxicity, neurotoxicity, metabolic disturbances such as diabetes mellitus and dyslipidemia, and cardiovascular complications such as hypertension and arrhythmias. Mycophenolate, a reversible inhibitor of inosine monophosphate dehydrogenase, frequently causes gastrointestinal disturbances, including diarrhea and colitis, as well as hematologic side effects like anemia and leukopenia, which increase infection risk. Therapeutic drug monitoring (TDM) and pharmacogenomics have emerged as essential strategies for mitigating these toxicities. TDM ensures tacrolimus trough levels are maintained within a therapeutic range, minimizing the risks of nephrotoxicity and rejection. Pharmacogenomic insights, such as CYP3A5 polymorphisms, allow for personalized tacrolimus dosing based on individual metabolic profiles. For mycophenolate, monitoring inosine monophosphate dehydrogenase activity provides a pharmacodynamic approach to dose optimization, reducing gastrointestinal and hematologic toxicities. Emerging tools, including dried blood spot sampling and pharmacokinetic modeling, offer innovative methods to simplify monitoring and enhance precision in outpatient settings. Despite their utility, the toxicity profiles of these drugs, including those of early immunosuppressants such as cyclosporine and azathioprine, necessitate further consideration of alternative immunosuppressants like sirolimus, everolimus, and belatacept. Although promising, these newer agents require careful patient selection and further research. Future directions in immunosuppressive therapy include integrating individual pharmacogenetic data to refine dosing, minimize side effects, and improve long-term graft outcomes. This narrative review underscores the importance of personalized medicine and advanced monitoring in optimizing post-transplant care.